A Simple Device and Biplanar Technique to Improve Precision When Templating for Total Joint Arthroplasty. Issue 3 (September 2021) - Chen, Foster; Giori, Nicholas
Abstract : Accurate templating for arthroplasty procedures depends on reliably estimating image magnification. The authors designed a simple device and technique to accomplish this. It is a wedge with four 25-mm balls staggered at different heights, each representing a potential marker. The proper ball to use as the scaling marker is identified on an orthogonal view on the basis of its relationship with the anatomic feature of interest. Reviewing x-rays with known acetabular component diameters, the authors found that the staggered balls technique had a scaling error of 1.48±0.89%. Assuming a constant 20% magnification for all x-rays resulted in an error of 1.65±1.59%. Although similarly accurate, the difference in precision was found to be significant ( P =0.012). The constant magnification method resulted in 2 outliers with >4% error, whereas there were no outliers with the novel technique. Staggered marker balls combined with orthogonal imaging is accurate and improves the precision of estimating radiograph magnification.